Regression model, artificial intelligence, and cost estimation for phosphate adsorption using encapsulated nanoscale zero-valent iron - Mahmoud, Ahmed S.; Mostafa, Mohamed K.; Nasr, Mahmoud (Separation science and technology, 2019)
This study investigated the adsorption of PO 4 3− onto encapsulated nanoscale zero-valent iron (nZVI). At initial PO 4 3- : 10 mg · L −1 , the optimum condition was initial pH: 6.5, nZVI dosage: 20 g · L −1 , stirring-rate: 100 rpm, and time: 30 min, achieving PO 4 3− removal of 42%. The effect of pH and time on the PO 4 3− removal efficiency was quadratic-linear concave up, whereas the curve of nZVI dosage was quadratic-convex. Artificial neural network with a structure of 5−7−1 adequately predicted PO 4 3− removal (R 2 : 97.6%), and the sensitivity analysis demonstrated that pH was the most influential input. The cost of the adsorption unit was 3.15 $USD · m −3 .